2022
DOI: 10.3390/world3030035
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Positive Deviant Farms Using Pareto-Optimality Ranking Technique to Assess Productivity and Livelihood Benefits in Smallholder Dairy Farming under Contrasting Stressful Environments in Tanzania

Abstract: In smallholder dairy-cattle farming, identifying positive deviants that attain outstanding performance can inform targeted improvements in typical, comparable farms under similar environmental stresses. Mostly, positive deviants are identified subjectively, introducing bias and limiting generalisation. The aim of the study was to objectively identify positive deviant farms using the Pareto-optimality ranking technique in a sample of smallholder dairy farms under contrasting stressful environments in Tanzania t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…The study builds on positive deviant farms earlier objectively identified in a large sample of farms using Pareto-Optimality ranking technique [18]. The positive deviant farms were isolated on criteria of consistently outperforming (p < 0.05) typical farms in five production performance indicators.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The study builds on positive deviant farms earlier objectively identified in a large sample of farms using Pareto-Optimality ranking technique [18]. The positive deviant farms were isolated on criteria of consistently outperforming (p < 0.05) typical farms in five production performance indicators.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, these were total energy balance to indicate the extent that cattle were experiencing feed scarcity, disease incidence density to indicate the extent that animals were exposed to disease infections while daily milk yield, age at first calving and calving interval indicated the extent of expression of production and functional traits. Shija et al [18] have detailed a stepwise process implemented to identify posi-…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations